Pengujian pada Aplikasi Penggajian Pegawai dengan menggunakan Metode Blackbox - Vadlan Febrian; Muhamad Rizki Ramadhan; Muhammad Faisal; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2020)
In this employee payroll application, if there is an error program there will be a loss for employees and the company. Losses for employees, if this application program error occurs then the salary reduction will experience delays due to the difficulty in the process of calculating employee salaries and employees will be late in receiving salaries. Losses for the company, if there is an error program in this application, the company will suffer losses if the employee wants a salary reduction quickly but the company cannot calculate quickly and accurately. In solving this problem, the authors use the black box testing method. Black box testing method is a test that sees the results of execution through test data and ensures the function of the software. Black box testing method has several testing techniques, namely Sample Testing, Boundary Value Analysis, Equivalence Partitions and others. From the testing techniques that have been mentioned, we use the Equivalence Partitions testing technique. Equivalence Partitions are tests that refer to data entry on the employee payroll application form, input will be tested and then put together based on the test function, both valid and invalid values. The expected results of this test are a payroll system for employees who are computerized, have standard rules in the process of developing the program so that it is easy to develop and maintain, and can minimize errors in processing salary calculations for employees.